DENTAL CERAMICS - MECHANICAL PROPERTIES - K Hynková; I Voborná (Czech Dental Chamber, 2022)
Introduction, aim: Ceramic is a mixture of inorganic non-metallic materials. The history of the ceramic is dated since Paleolithic age. It is used, for example for production of jewelry, dishes, the construction industry, sculpturing and of course in dentistry. Ceramic is hard, strong, thermal and electrical nonconductive and it has an aesthetic appearance. Due to increasing patient's demands for beautiful and natural smile, the ceramic is a good choice for this aesthetics work. The ceramic mimics very well the optical features of hard dental tissues such as enamel and dentin. Therefore, ceramic becomes a material, which is used every day in dental labs. It is used for production of all-ceramic, porcelain fused to metal (PFM), and core crowns or bridges, inlays, onlays, aesthetic veneers, and also fixtures and supra-constructions of dental implants. The selection of ceramic for the required ceramic work should not only include the aesthetics of the future ceramic work, it is also important to consider mechanical properties of the ceramic. Occlusion forces increase in the oral cavity from frontal to lateral segment while the demands for aesthetics decrease in this direction. The ceramics which is a suitable solution for frontal segment, might not be suitable for lateral segment and vice versa. That is why the objective of our paper is to describe, compare and classify some mechanical properties of ceramic used in dentistry. Methods: For our review focused on mechanical properties of ceramics we collected the relevant data from specialized books and literature dealing with the topic of ceramic available in the PubMed database. These studies were critically evaluated for this review. Conclusion: The knowledge of mechanical properties of dental ceramic is crucial. Thanks to this knowledge, dentist can choose suitable material, which best meets specific requirements for dental restoration. On the other hand, the ignorance can lead to unsatisfactory results up to failure of dental restoration.